1981
DOI: 10.1249/00003677-198101000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Shot Putting Technique

Abstract: Purposes: Analysis of the Chinese women's shot player Xiangrong LIU 2016 national track and field throwing group race (Xipu station) champion throwing action, revealing the law of shot put. Procedures: Application data engineering method-with two JVC GC-PX10AC cameras were placed in the direction of throwing and positive right, two cameras, the main axis of the angle of about 90 °, shooting frequency of 50Hz. Using Signal TEC 3D software to analyze the kinematic parameters. Methods:Three-dimensional video anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 0 publications
3
35
1
3
Order By: Relevance
“…). Although CMJ performance is not directly transferred to the dive start (11,20), our results agree with those of Zatsiorsky et al (37), who showed a correlation between flight time and the swimmer's jumping ability (r = 0.68). Similarly, Counsilman et al (13), Miyashita et al (27), and Pearson et al (28) noted a significant correlation between swim start performance and vertical jumping or leg extensor power.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…). Although CMJ performance is not directly transferred to the dive start (11,20), our results agree with those of Zatsiorsky et al (37), who showed a correlation between flight time and the swimmer's jumping ability (r = 0.68). Similarly, Counsilman et al (13), Miyashita et al (27), and Pearson et al (28) noted a significant correlation between swim start performance and vertical jumping or leg extensor power.…”
supporting
confidence: 91%
“…Zatsiorsky et al (37) noted 2 styles of conventional start (forward and full arm swing), whereas Lewis (23) observed 3 (arms back, straight arm backswing, and circular arm backswing). According to Bowers and Cavanagh (10) and Lewis (23), the conventional start enables longer flight distances than the grab start but at the expense of a longer block phase; the conventional start was therefore advised in the relay where the block time is not necessarily incorporated into the performance time.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the delivery phase in track and field throws ranges between 150-250 ms [3,[39][40][41]. Chronic exercise training adaptations may have increased the late RFD ability of these athletes rendering them to perform better relative to their musculature as compared to taekwondo athletes, as found in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…Explosive strength may be evaluated with the rate of force development (RFD; i.e., the slope of the tangent line of the force/torque-time curve during an explosive muscle contraction [1,2]), which has been linked with explosive sports performance. Indeed, lower body isometric leg press RFD at 100, 150, 200, and 250 ms from the onset of contraction, is associated with performance in track and field throwers, where the time for the final delivery of the implement is between 150-250 ms [3]. Taekwondo is also considered to be a powerful sport.…”
Section: Introductionmentioning
confidence: 99%
“…Other principle of movement organization which was reviewed in the study was sequential action of muscle groups and body segments. Sequential action of body segments principle in tennis strokes anticipates achievement of three strategies: 1) body segment joining the movement in the proper moment; 2) operation in the direction from proximal to distal body segments; 3) active braking of the body segments in the finish of the stroke (Hochmuth, 1964;Dyson, 1978;Lanka, 2003;Winter, 1979;Zatsiorsky et al, 1982;Ivanicevic et.al., 2011). The above consists of two mechanisms -muscle-tendon complex pre-stretch and consecutive acceleration and braking of body segments, in sports literature is called whip technique or whip mechanism (Lanka, 2003;Kopsic Segal, 2003;Ivancevic et al, 2011;Шалманов, 2002).…”
Section: Discussionmentioning
confidence: 99%